2016
DOI: 10.3389/fpls.2016.00904
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Root WSC during Grain Filling in Wheat under Drought

Abstract: As the first organ in plants to sense water-deficit in the soil, roots have important roles for improving crop adaption to water limited environments. Stem water soluble carbohydrates (WSC) are a major carbon source for grain filling under drought conditions. The contributions of root WSC during grain filling under drought has not been revealed. Wheat parental lines of Westonia, Kauz and their derived four double haploid (DH) lines, namely, DH 125, DH 139, DH 307, and DH 338 were used in a field drought experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…In agreement with previous research on Kauz and Westonia [9], a major component of the plant WSC is stored in the stem. In the current study, the WSC level in stems is double that in the leaves, and the accumulation of stem WSC is mainly based on the increment in fructan concentrations in the stems (82% of stem WSC).…”
Section: Associations Between Leaf Senescence and Wscsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous research on Kauz and Westonia [9], a major component of the plant WSC is stored in the stem. In the current study, the WSC level in stems is double that in the leaves, and the accumulation of stem WSC is mainly based on the increment in fructan concentrations in the stems (82% of stem WSC).…”
Section: Associations Between Leaf Senescence and Wscsupporting
confidence: 92%
“…The major phenotypic contributors to wheat grain yield are thousand grain weight (TGW) and kernel number per spike (KN) [2][3][4]. The sum of glucose, fructose, sucrose and fructans, hereafter termed "water soluble carbohydrate" (WSC) in wheat stems and leaf sheaths is one of the crucial parameters contributing to grain yield especially under terminal drought conditions [5][6][7][8][9]. Interestingly, the remobilization of stem WSC is subject of considerable genetic variation, and molecular marker screening has been useful in identifying suitable lines for pre-breeding [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Food and Agriculture Organization of the United Nations, Human farming, grazing took possession of 25-30%. Humans cannot effectively use the remaining dry land for plant production (Hu and Xiong, 2014;Zhang et al, 2016). Thus, it is urgent to clarify effect of drought stress on growth and development of wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise the activity of adenosine diphosphate-glucose pyrophosphorylase (AGPase) is associated with grain filling [29] and under drought conditions an increased activity of AGPase within the grains of wheat and rice was reported by Yang et al [14]and Zhang et al [30]. Under drought stress, translocation of limited carbohydrates from source tissues to grains [31] and; from sink tissues to grains is important to determine the grain yield under stress [32]. Li et al [33] reported an increase in the activity of spike phosphoglucomutase and aldolase under high CO 2 indicating the role carbohydrate metabolism within spike in response to an enhanced source activity.…”
Section: Introductionmentioning
confidence: 95%